Evaluation of quasi-static and dynamic nanomechanical properties of bone-metastatic breast cancer cells using a nanoclay cancer testbed - Sumanta Kar (Nature Portfolio, 2021)
Abstract In recent years, there has been increasing interest in investigating the mechanical properties of individual cells to delineate disease mechanisms. Reorganization of cytoskeleton facilitates the colonization of metastatic breast cancer at bone marrow space, leading to bone metastasis. Here, we report evaluation of mechanical properties of two breast cancer cells with different metastatic ability at the site of bone metastases, using quasi-static and dynamic nanoindentation methods. Our results showed that the significant reduction in elastic modulus along with increased liquid-like behavior of bone metastasized MCF-7 cells was induced by depolymerization and reorganization of F-actin to the adherens junctions, whereas bone metastasized MDA-MB-231 cells showed insignificant changes in elastic modulus and F-actin reorganization over time, compared to their respective as-received counterparts. Taken together, our data demonstrate evolution of breast cancer cell mechanics at bone metastases.